Developmental Changes in Empathic Concern and Self-Understanding in Toddlers at Genetic Risk for Autism Spectrum Disorder - Campbell, Susan B. (J Autism Dev Disord, 2017)
Toddlers with an older sibling with autism spectrum disorder (ASD) and low risk (LR) toddlers were observed at 22, 28, and 34 months during two empathy probes: concern for a crying baby and an adult who pretended to hurt her finger. Toddlers with a later ASD diagnosis showed less empathic concern and self-distress at each age on both empathy probes than LR toddlers. HR toddlers with no diagnosis showed growth in empathic concern between 22 and 34 months in response to the adult’s pain, differing from the children with ASD, but not the LR children, by 34 months. Developmental changes in parent-rated self-understanding showed a similar pattern. Results highlight individual differences in the social development of HR toddlers.